Six Unrecorded Species of Agaricales (Agaricomycetes, Basidiomycota) from Mudeungsan National Park in Korea - Minseo Cho; Yeonjae Yoo; Sang Hyun Lee; Dae Young Kwon; Changmu Kim; Sun Lul Kwon; Jae-Jin Kim (Mycobiology, 2025)
The order Agaricales is one of the diverse mushroom-forming fungi, with approximately 40,000 identified species worldwide. They contribute to forest ecosystems as decomposers, symbionts, or pathogens. Mudeungsan National Park is one of the biggest National Park in Southwestern Korea. However, the diversity of macrofungi has been less studied than the diversity of flora and fauna. Thus, we collected macrofungal specimens through surveys in Mudeungsan National Park from 2020 to 2023. The specimens were identified based on the morphological characteristics, and phylogenetic analysis using internal transcribed spacer (ITS) and nuclear large subunit ribosomal DNA (nLSU) regions. As a result, six unrecorded Agaricales species were identified: Agaricus parvibicolor, Clitopilus subscyphoides, Deconica cokeriana, Hohenbuehelia tristis, Mycena heteracantha, and M. silvae-nigrae. In this study, we provide detailed figures and phylogenetic trees to support six unrecorded Agaricales species in Mudeungsan National Park.